Assessment the Presence of PolyCystic Ovary syndrome (PCOs)’s Symptoms among Hama University- Nursing Faculty’s Female Students and their Level of Knowledge about it - نظام عفاف عيسى (Latakia University Journal -Medical Sciences Series, 2021)
PolyCystic Ovarian syndrome (PCOs) in its most common form of hyperandrogenism and chronic anovulation is one of the most important female endocrine disorders, its affecting approximately (5-10)% of women of childbearing age, and despite of it; there are still some groups of society suffer from a lack of knowledge about the syndrome and how to deal with it, which will negatively affect the chronic course of it. The aim of this study is to assess presence of syndrome symptoms and the knowledge level about PCOs among female students in Nursing Faculty - Hama University. The study was conducted by distributing a questionnaire to the available female students in the first and second year of the mentioned faculty; while they were in their classrooms. The results indicated that the 37.1% of the sample suffer from a partial absence of a menstrual period, 58.4% suffer from acne problems during their menstrual cycle, 12.4% have unusual hair growth on the male pattern, and 40.4% had unusual hair loss; while their knowledge level about PCOs was between medium and weak. The study recommended the necessity of conducting educational programs targeting female students in schools and universities to support their information about PCOs, in addition to support mothers’s information about their dughter’s reproductive system diseases through health centers, and conduct more studies to determine the factors that affect students’ information about the syndrome.